Mastering test writing skills internet research techniques - Mattox, Philip; Pallardy, Micheal; The School company; The Princess Company ([Jackson, WY] : The Princess Company, 2003)
This video addresses the critical thinking process that helps easily distinguish relevant sources from the clutter
Executive producer, Philip Mattox ; producer, Micheal Pallardy ; writer, editor, Julie Ringold
Educator : Stacy Hill, Julie Ringold
Host : Nike Imarla
Keywords: Internet research; Internet searching; Computer network resources